FIGURATIVE LANGUAGE IN THE WEEKND’S MY DEAR MELANCHOLY - Damardjati , Lanang; Hardiany , Dewi Rosnita (Universitas Ngudi Waluyo, 2023)
The relationship between language and lyrics is fascinating, since music and language's blend together.